2017
DOI: 10.22271/ortho.2017.v3.i2f.59
|View full text |Cite
|
Sign up to set email alerts
|

Open interlocking nailing of the fracture of the shaft of femur

Abstract: Fracture neck of femur has always attracted the mankind due to its peculiar nature of going into non union and osteonecrosis of femoral head even with best fixation method and adequate reduction. A novel way to treat fracture neck of femur is with small diameter dynamic hip screw and an additional derotation screw. 30 patients aged 18-60 years presenting to Deen Dayal Upadhyay Hospital with fresh (<3 weeks old) fracture neck of femur were randomized into two groups and were treated with two different modalitie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…While closed interlocking nail remains the gold standard in the treatment of femoral shaft fractures, open Kuntscher nailing may still have its relevance in the developing countries as reported by other author. 14,15 Maruenda-Paulino JI et al 16 after their study concluded usefulness of Kuntscher nailing in children and adolescents with unstable high velocity fracture of the femoral shafts. It was concluded that open Kuntscher nailing is a method still relevant in situations like poor patients, high risk patients and when interlocking nailing of femoral shaft fracture may not feasible.…”
Section: Resultsmentioning
confidence: 98%
“…While closed interlocking nail remains the gold standard in the treatment of femoral shaft fractures, open Kuntscher nailing may still have its relevance in the developing countries as reported by other author. 14,15 Maruenda-Paulino JI et al 16 after their study concluded usefulness of Kuntscher nailing in children and adolescents with unstable high velocity fracture of the femoral shafts. It was concluded that open Kuntscher nailing is a method still relevant in situations like poor patients, high risk patients and when interlocking nailing of femoral shaft fracture may not feasible.…”
Section: Resultsmentioning
confidence: 98%
“…Some Sha S et al authors advocate open nailing in the poly-trauma pa ent and first-trimester pregnant pa ent for the least radia on exposure because it requires no special equipment and achieves quick reduc on. ORIF is performed in certain situa ons like unavailability of C-arm fluoroscopy, trac on table, minimal resources, to avoid radia on hazards, early disposal of the pa ent, and overcrowded orthopedic 10,11 wards.…”
Section: Discussionmentioning
confidence: 99%